On Jurisdictional Proceedings and the Concept of a Party in the Code of Administrative Procedure - Zimmermann, Marian (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2021)
The paper is an English translation of Z rozważań nad postępowaniem jurysdykcyjnym i pojęciem strony w kodeksie postępowania administracyjnego by Marian Zimmerman published originally in „Księga pamiątkowa ku czci Kamila Stefki” in 1967. The text is published as a part of a section of the Adam Mickiewicz University devoted to the achievements of the Professors of the Faculty of Law and Administration of the Adam Mickiewicz University, Poznań.